The Architect as a Social Designer: The Fun Palace Case - Popov, Lubomir Savov; David, Gary (Enquiry The ARCC Journal for Architectural Research, 2015)
The goal of this paper is to discuss how the architectural profession and its work, through development of physical structures, relate to the idea of social design. Toward this end, we explore a number of issues that emerge from this concept”the social role of the architect, the emerging engagements in social design, and the need for corresponding design ethics. Through an applied sociological approach that focuses on interaction, emphasizing collaborative and transformative work within situated contexts, we conduct a case study on a project known as The Fun Palace. Rather than providing a detailed examination of the Fun Palace or its architect, Cedric Price, this paper uses this case to explore and discuss the potential for architecture in social design. Consequently, the study contributes to the ongoing debate on the social role of the architect, the scope of the architectural profession, and involvement with social design.